The Effect of Counseling Using Pop-Up Book Media on Mothers' Knowledge and Attitudes in Fulfilling Nutrition for Children Aged 1-3 Years in the Working Area of the Juli II Health Center, Bireuen District - Nisrina, Naifa Naja; Arnisam, Arnisam (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2025)
According to Indonesia's SSGI 2022 data, 17.1% of underweight toddlers, particularly in developing countries, suffer mortality related to inadequate dietary intake. Juli II Health Center in Bireuen District reports a 10.0% prevalence of undernutrition among its target of 1,450 toddlers, consisting of 6.6% underweight and 3.4% wasting. Maternal knowledge and attitudes significantly impact child nutritional health and are critical targets for educational intervention. This study aimed to assess the effect of counseling using pop-up book media on mothers’ knowledge and attitudes regarding nutrition for children aged 1–3 years. This quasi-experimental study employed a one-group pretest-posttest design with a non-probability quota sampling method, involving 30 mothers. Data were collected using structured pretest and posttest questionnaires and analyzed using the Wilcoxon signed-rank test. The results showed that the average maternal knowledge score increased from 8.27 (SD=3.657) to 13.37 (SD=1.189), and the average attitude score rose from 43.63 (SD=3.296) to 55.00 (SD=3.904). Statistical analysis indicated significant differences before and after intervention (p=0.000). The study concludes that pop-up book media effectively improve maternal knowledge and attitudes related to fulfilling nutritional needs for toddlers.